Design, synthesis, and biological investigation of selective human carbonic anhydrase II, IX, and XII inhibitors using 7-aryl/heteroaryl triazolopyrimidines bearing a sulfanilamide scaffold - Romagnoli, Romeo; De Ventura, Tiziano; Manfredini, Stefano; Baldini, Erika; Supuran, Claudiu T; Nocentini, Alessio; Brancale, Andrea; Bortolozzi, Roberta; Manfreda, Lorenzo; Viola, Giampietro (Journal of enzyme inhibition and medicinal chemistry, 2023)
A novel library of human carbonic anhydrase (hCA) inhibitors based on the 2-sulfanilamido[1,2,4]triazolo[1,5-a]pyrimidine skeleton modified at its 7-position was prepared by an efficient convergent procedure. These derivatives were evaluated in vitro for their inhibition properties against a representative panel of hCA isoforms (hCA I, II, IV, IX, and XII). The target tumour-associated isoforms hCA IX and XII were potently inhibited with KIs in the low nanomolar range of 5-96 nM and 4-72 nM, respectively. Compounds 1d, 1j, 1v, and 1x were the most potent hCA IX inhibitors with KIs of 5.1, 8.6, 4.7, and 5.1 nM, respectively. Along with derivatives 1d and 1j, compounds 1r and 1ab potently inhibited hCA XII isoform with KIs in a single-digit nanomolar range of 8.8, 5.4, 4.3, and 9.0 nM, respectively. Compounds 1e, 1m, and 1p exhibited the best selectivity against hCA IX and hCA XII isoforms over off-target hCA II, with selectivity indexes ranging from 5 to 14.
Keywords: Carbonic Anhydrase I; Carbonic Anhydrase Inhibitors; molekulární struktura; karboanhydrasa II; karboanhydrasa I; vztahy mezi strukturou a aktivitou; antigeny nádorové; Sulfanilamides; karboanhydrasa IX; lidé; sulfanilamidy; Structure-Activity Relationship; Carbonic Anhydrase IX; inhibitory karboanhydras; Humans; protein - isoformy; Carbonic Anhydrase II; Antigens, Neoplasm; Molecular Structure; Protein Isoforms